Self‐repair behaviour of the neuronal cell membrane by conductive atomic force indentation. Issue 9 (23rd September 2019) - Liu, Caijun; Han, Xueyan; Yang, Xueying; Tian, Liguo; Wang, Ying; Wang, Xinyue; Yang, Huanzhou; Ge, Zenghui; Hu, Cuihua; Liu, Chuanzhi; Song, Zhengxun; Weng, Zhankun; et al.
Abstract : Conductive atomic force indentation (CAFI) was proposed to study the self‐repair behaviour of the neuronal cell membrane here. CAFI was used to detect the changes of membrane potentials by performing the mechanical indentation on neurons with a conductive atomic force microscope. In the experiment, a special insulation treatment was made on the conductive probe, which turned out to be a conductive nanoelectrode, to implement the CAFI function. The mechanical properties of the neuronal cell membrane surface were tested and the membrane potential changes of neurons cultured in vitro were detected. The self‐repair behaviour of the neuronal cell membrane after being punctured was investigated. The experiment results show that CAFI provides a new way for the study of self‐repair behaviours of neuronal cell membranes and mechanical and electrical properties of living cells.